Synthesis and biological evaluation of N-(3-fluorobenzyl)-4-(1-(methyl-d3)-1H-indazol-5-yl)-5-(6-methylpyridin-2-yl)-1H-imidazol-2-amine as a novel, potent ALK5 receptor inhibitor. (1st April 2023) - Kang, Byung-Nam; Kang, Hong-Jun; Kim, Sunjoo; Lee, Jungwoo; Lee, Jinwoo; Jeong, Hee-Jin; Jeon, Seeun; Shin, Youngdo; Yoon, Cheolhwan; Han, Cheolkyu; Seo, Jeongbeob; Yun, Jaesook
Graphical abstract: Abstract: Specific inhibition of ALK5 provides a novel method for controlling the development of cancers and fibrotic diseases. In this work, a novel series of N -(3-fluorobenzyl)-4-(1-(methyl-d3 )-1 H -indazol-5-yl)-5-(6-methylpyridin-2-yl)-1 H -imidazol-2-amine (11 ), a potential clinical candidate, was synthesized by strategic incorporation of deuterium at potential metabolic soft spots and identified as ALK5 inhibitors. This compound has a low potential for CYP-mediated drug-drug interactions as a CYP450 inhibitor (IC50 = >10 μM) and showed potent inhibitory effects in cellular assay (IC50 = 3.5 ± 0.4 nM). The pharmacokinetic evaluation of 11 in mice demonstrated moderate clearance (29.0 mL/min/kg) and also revealed high oral bioavailability in mice ( F = 67.6%).